HANDLING DATA OF POLIO IMMUNIZATION IN ACEH: A COMMUNITY SERVICE - Dharina Baharuddin; Riza Septiani; Iman Murahman (ABDIMU: Jurnal Pengabdian Muhammadiyah, 2023)
The polio outbreak re-emerged in Aceh Province, Indonesia, in 2022, specifically in Pidie District. The main cause of this outbreak was the low immunization coverage in this province. The Indonesian government responded to this outbreak by providing mass vaccination of Novel Oral Polio Vaccine type 2 (nOPV2) to children under 13 years old. Polio vaccine recipients must be accurately recorded in an online application called the Aplikasi Sehat Indonesia-Ku (ASIK). The goal of this community service was to ensure that this data was accurately recorded in the ASIK system. Workshops or training have been conducted three times for polio vaccine recipient data enumerators and immunization staff throughout the districts in Aceh from December 2022 to February 2023. This activity successfully motivated enumerators and all immunization staff in Aceh to record 986,071 data, demonstrating significant progress in outbreak monitoring and informed decision-making. This success was expected to support effective measures in handling the polio outbreak in the province of Aceh.